Nutritional Status in Dysphagic and Nondysphagic Elderly Persons in Turkey: A Comparison Study - Bayram, Hatice Merve; Ilgaz, Fatma; Serel-Arslan, Selen; Demir, Numan; Rakıcıoğlu, Neslişah (Progress in Nutrition, 2021)
Aim: Dysphagia can directly affect one’s food intake, leading to weight loss and malnutrition. This study aimed to investigate the association of dysphagia with nutritional status in elderly persons. Methods: This was a descriptive and cross-sectional study including case and control groups. It was conducted in the Hacettepe University Hospitals in Turkey between April 2015-2016. The research sample comprised volunteers aged >65 years who met the study criteria. The study included 55 elderly persons with dysphagia (49.1% male) and 62 without dysphagia (38.7% male) in Hacettepe University Hospitals. The dysphagia risk was evaluated with the Eating Assessment Tool. The dietary intake was recorded by 24-hour dietary recall and anthropometric measurements (body weight and hand-grip strength in kilograms; height, waist circumference and mid upper arm circumference in centimeters; and triceps skinfold thickness in millimeters). Study data were evaluated with the statistical program SPSS 23.0. Results: The body weight, body mass index and waist circumference were greater in the control group than the dysphagic males. The mid upper arm circumference, hand-grip strength and muscle area were greater for both genders in the control group than the dysphagic group. According to the Mini Nutritional Assessment, the percentages who were malnourished or at risk of malnutrition were 49.1% and 45.4%, respectively in the dysphagic group, and 9.7% and 41.9% respectively in the control group. In both groups, the vitamin B1, niacin, folate, calcium, magnesium and zinc intake were inadequate according to RDA. In addition, in the dysphagic group, the daily intake of energy, fiber, vitamins B1, B2, B6, niacin, folate, calcium, magnesium, iron and zinc was found to be inadequate according to the RDA. Conclusion: Dysphagia has a great impact on the nutritional risk and malnutrition and also may be responsible for nutritional deficiencies in elderly persons because nutritional deficiencies are common comorbidities of dysphagia in this age group, regular nutritional monitoring should be part of the geriatric care plan.